Pemanfaatan Tanaman Bambu dan Kaliandra untuk Perkuatan Lereng sebagai Upaya Mitigasi terhadap Longsor di Desa Sinarresmi Sukabumi: Utilization of Bamboo and Kaliandra Plant for Slope Reinforcement as a Mitigation Effort against Availability in Sinarresmi Village, Sukabumi - Zayadi, Ruwaida; Andayani, Sih; Indrawati, Etty (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The PKM program, with the theme of community empowerment in sustainable environmental management with the title "Utilization of bamboo and calliandra plants for slope reinforcement as a mitigation effort against landslides in Sinaresmi Sukabumi Village," aims to provide a solution to the housing conditions of the residents of the Traditional Village of Sinarresmi Sukabumi Village, after the occurrence of a landslide disaster in 2019 which left the slopes of the hilly area vulnerable to landslides. The methods used are Providing education, knowledge, and understanding that forms awareness of the dangers of landslides and how to prevent them with cheap, easy, and environmentally friendly methods; providing training by assisting in making retaining walls (slope reinforcement) using natural resources around residential areas, namely bamboo stems and Kaliandra plant cuttings. The result of this PkM activity is the emergence of an awareness of the Indigenous Village community about the need for landslide disaster mitigation by strengthening landslide-prone slopes with materials around the dwelling. The conclusion of the PkM is the emergence of community awareness in mitigating landslide disasters through the skills to make slope reinforcement based on nature that is cheap, easy, and has ecological value. This service activity also urges the community to preserve bamboo plants by revegetation. The advantage of this PkM is that it involves the traditional village community, uses local natural resources, and can be applied in other areas.